The use of waterfalls and its implications for the indoor environment (Tourist restaurants as a model) (Journal of the College of Basic Education, 2020)
The importance of research comes from the study of water formations resulting from the water of the waterfall and its effects and the rest of the vocabulary of the interior design to the level of functional aesthetic in order to improve the design process, The objectives of this study are to determine the effects of water flow and the ways in which they flow in order to reach the most suitable employment within water units to form the most effective effect visually and audio and to reveal their relationship functionally and inwardly with the interior design of tourist restaurant halls. The third chapter was devoted to the description of the samples and questionnaire form and designed by the researcher. Five experts were consulted in the field of design and study of the four samples from the research community. The results of the research were assigned to the fourth chapter of the research, where the samples were analyzed by the researcher in the light of the paragraphs of the questionnaire form and to derive the percentages achieved and non-achieved in the eyes selected deliberately, through which the researcher reached a set of conclusions, conclusions, recommendations and proposals.